Optic nerve sheath enhancement in patients with a new diagnosis of idiopathic intracranial hypertension - Labella Álvarez, Fernando; Saindane, Amit M.; Biousse, Valérie; Newman, Nancy J. (Frontiers in Neurology, 2025)
IntroductionOptic nerve sheath enhancement (ONSE) is a radiologic sign commonly associated with a diagnosis of optic perineuritis. However, recent studies have reported this radiologic sign in patients with idiopathic intracranial hypertension (IIH). The presence of ONSE in patients with IIH may lead to optic perineuritis diagnosis in excess. We evaluated the prevalence of ONSE in patients with a new diagnosis of IIH.MethodsRetrospective study of consecutive patients who presented to the emergency department of our quaternary care center with a suspected intracranial pressure disorder between June 15, 2023 and July 1, 2024. Patients who received a new diagnosis of IIH fulfilling the 2013 revised diagnostic criteria and who underwent orbital magnetic resonance imaging (MRI) with fat-suppressed contrast-enhanced sequences were included. An expert neuroradiologist evaluated all orbital MRIs for the presence of ONSE.ResultsForty-three patients with a new diagnosis of IIH were included (mean age, 31 ± 7 years; 100% women; 72% Black, 20% White, and 8% other). Of these 43 patients, three were categorized as having suggested ONSE versus blood vessels. The remaining 40 patients were categorized as having no ONSE.DiscussionONSE is a radiologic sign that may occur in approximately 7% of patients with newly diagnosed IIH. However, the distinction between mild ONSE and blood vessels surrounding or within the optic nerve sheath is challenging. A location at the distal infraorbital portion of the optic nerve sheath and a corkscrew appearance are suggestive of a vascular etiology. Awareness of this radiologic sign in patients with IIH is important to avoid optic perineuritis diagnosis in excess.